Effects of Paroxetine, Bupropion or Agomelatine on Ovarian Tissue and Anti-Mullerian Hormone Levels in Female Rats - Ulker, Nazife; Yardimci, Ahmet; Kaya, N.; Bulmus, Funda Gulcu; Colakoglu, Neriman; Sahin, Zafer; Kelestimur, Haluk (Karger, 2018)
[Abstract Not Available]
3rd International Congress of the Turkish-Neuroendocrinology-Society -- JUN 29-JUL 01, 2018 -- Malatya, TURKEY